Frog Thrombocytes Aggregation and the Release Reaction - Stiller, Ronald A.; Belamarich, Frank A.; Shepro, David (Thrombosis and Haemostasis, 1974)
Frog thrombocytes were shown to aggregate in response to thrombin, collagen, and adenosine triphosphate (ATP). Microscopic observations indicated that collagen and thrombin induced aggregates were cell-to-cell in nature and not due solely to passive adherence to collagen or fibrin strands.The ability of ATP to promote aggregation suggested that the release of this nucleotide might be the mechanism by which frog thrombocytes aggregate ; however, there was no evidence to support this hypothesis. Enzymatic hydrolysis of ATP by hexokinase had no effect on thrombin-induced aggregation, and ATP could not be identified in the supernatants of aggregated thrombocytes. Nevertheless, the ability of these cells to aggregate in response to these aggregating agents indicates that significant parallels may exist between platelet aggregation and the aggregation of non-mammalian thrombocytes.